Electrochemical device and electronic device
By using a composite liquid collector and characteristic negative electrode material layer in lithium-ion batteries, the two-way transmission of lithium ions is achieved, which solves the problem of uneven charge state of the negative electrode material layer and improves the rate performance of the battery.
Patent Information
- Application Number
- CN202411719502.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
The negative electrode material layer of existing lithium-ion batteries has uneven charge states, which limits the battery's rate performance.
Using a composite liquid collector and an anode material layer, the composite liquid collector has good lithium ion conductivity, and the characteristic peak intensity of the XRD spectrum of the anode material layer is within a specific range, realizing bidirectional transmission of lithium ions.
The charge state uniformity of the negative electrode material layer is improved and the rate performance of the electrochemical device is improved.
Smart Images

Figure CN119542511A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemistry, and in particular to an electrochemical device and an electronic device. Background Art
[0002] Electrochemical devices, such as lithium-ion batteries, have traditional negative electrode current collectors made of copper foil, which have no pores and cannot penetrate electrolyte. During the charging process, the transmission direction of lithium ions on the negative electrode material layer is only from the negative electrode material layer far from the negative electrode current collector to the negative electrode material layer near the negative electrode current collector, resulting in a higher state of charge in the negative electrode material layer far from the negative electrode current collector in the fully charged state, and a lower state of charge in the negative electrode material layer near the negative electrode current collector. The overall state of charge of the negative electrode material layer is relatively non-uniform, thus limiting the rate performance of lithium-ion batteries. At present, the main ways to improve the distribution of the state of charge of the negative electrode material layer include increasing the porosity of the negative electrode material layer, constructing a directional pore structure, etc. However, increasing the porosity of the negative electrode material layer will reduce the energy density of the battery, and constructing a directional pore structure will increase the process difficulty and cost of the preparation process of the negative electrode material layer, which is not suitable for large-scale production. In addition, the lithium ion transmission direction of the above two methods is still single-sided transmission, and there is still a large state of charge gradient between the direction away from the negative electrode current collector and the direction close to the negative electrode current collector. Summary of the invention
[0003] The purpose of the present application is to provide an electrochemical device and an electronic device to improve the non-uniformity of the overall charge state of the negative electrode material layer, thereby improving the rate performance of the electrochemical device.
[0004] It should be noted that in the invention content of this application, lithium-ion batteries are used as an example of electrochemical devices to explain this application, but the electrochemical devices of this application are not limited to lithium-ion batteries. The specific technical solutions are as follows:
[0005] The first aspect of the present application provides an electrochemical device, which includes a pole piece, the pole piece includes a composite current collector and a negative electrode material layer located on the surface of the composite current collector, the XRD spectrum of the negative electrode material layer has a characteristic peak intensity of I1 at 23.5° to 24.5°, and a characteristic peak intensity of I2 at 24.5° to 25.5°; the thickness of the negative electrode material layer is Lμm, and along the thickness direction of the negative electrode material layer, the distance from any point in the negative electrode material layer to the negative electrode current collector is Zμm, and at Z=0.5L±0.1L, I1 / I2 reaches a minimum value; the ionic conductivity σ of the composite current collector is ion For 10 - 4 S / m≤σ ion ≤10 -1The composite current collector has good lithium ion conductivity, and bidirectional lithium ion transmission can be achieved inside the negative electrode material layer, which is beneficial to improving the overall non-uniformity of the charge state of the negative electrode material layer, and further beneficial to improving the rate performance of the electrochemical device.
[0006] In some embodiments of the present application, at Z=0.5L±0.1L, 10≤I1 / I2≤30. When the charge rate is 0.5C to 5C, at the negative electrode material layer Z=0.5L±0.1L, 10≤I1 / I2≤30.
[0007] In some embodiments of the present application, when the charge rate is 5C, along the thickness direction of the negative electrode material layer, the difference between the maximum and minimum values of I1 / I2 in the negative electrode material layer is less than or equal to 30. The difference between the maximum and minimum values of I1 / I2 in the negative electrode material layer is within the above range, indicating that the overall charge state uniformity of the negative electrode material layer is high, which is beneficial to improving the rate performance of the electrochemical device.
[0008] In some embodiments of the present application, the thickness of the negative electrode material layer is 30 μm to 180 μm.
[0009] In some embodiments of the present application, the thickness of the negative electrode material layer is 40 μm to 120 μm.
[0010] In some embodiments of the present application, the negative electrode material layer includes a negative electrode active material, and the negative electrode active material includes at least one of graphite, graphite silicon carbon composite material, graphite hard carbon composite material or graphite soft carbon composite material. The above negative electrode active material has a high specific capacity, which is conducive to improving the energy density of the electrochemical device and improving the cycle performance.
[0011] In some embodiments of the present application, the composite current collector includes a substrate and a conductive layer located on the surface of the substrate, the substrate includes any one of a porous polymer high molecular film, a polymer solid electrolyte membrane or a composite solid electrolyte membrane, and the conductive layer is selected from a metal layer or a conductive carbon layer. The above-mentioned substrate has good lithium ion conductivity, and the arrangement of the conductive layer makes it have good conductivity, so that during the charging process of the electrochemical device, it is beneficial to improve the overall charge state non-uniformity of the negative electrode material layer, and further to improve the rate performance of the electrochemical device.
[0012] In some embodiments of the present application, the porous polymer film includes a polymer; the polymer solid electrolyte film includes a lithium salt and the polymer; the composite solid electrolyte film includes an inorganic solid electrolyte and the polymer. The above-mentioned types of substrates have good lithium ion conductivity, which is conducive to improving the overall charge state non-uniformity of the negative electrode material layer during the charging process of the electrochemical device, and further helps to improve the rate performance of the electrochemical device.
[0013] In some embodiments of the present application, the polymer includes at least one of polypropylene, polyethylene terephthalate, polystyrene, polyethylene, poly(p-phenylene terephthalamide), polyethylene oxide, polymethyl methacrylate, polyacrylonitrile, polyvinylidene fluoride or polyvinylidene fluoride-hexafluoroethylene; the lithium salt includes at least one of LiPF6, LiN(CF3SO2)2, LiN(FSO2)2, LiCF3SO3 or LiClO4; the inorganic solid electrolyte includes at least one of a sulfide solid electrolyte or an oxide solid electrolyte; the sulfide solid electrolyte includes (100-x1)Li2S-x1P2S5, Li 4-x2 Ge 1-x2 P x2 S4、LiPSCl 0.8 、LiPSCl 1.3 、LiPSCl 1.5 or LiPSCl 1.6 At least one of; wherein 1≤x1≤99, 0.01≤x2≤0.99; the oxide solid electrolyte comprises (a) Li 1+x3 M x Ti 2-x3 (PO4)3、Li 1.5 Z 0.5 Ge 1.5 (PO4)3、Li 7-3x4 Ga x4 La3Zr2O 12 、Li7La3Zr2O 12 , Li 6.55 Ga 0.15 La3Zr2O 12 or Li 0.34 La 0.51 TiO 2.94At least one of; wherein, M includes at least one of Al, Cr, Ga, Fe, Sc, In, Lu, Y or La, 0≤x3≤0.5, Z includes at least one of Al, Cr, Ga, Fe, Sc, In, 0.1≤x4≤0.4. By selecting the above materials, the obtained substrate has good lithium ion conductivity, which is beneficial to improve the overall charge state non-uniformity of the negative electrode material layer during the charging process of the electrochemical device, and further helps to improve the rate performance of the electrochemical device.
[0014] In some embodiments of the present application, the material of the metal layer includes any one of copper, nickel or silver. The metal layer has good electrical conductivity, and the obtained composite current collector also has good electrical conductivity, which is beneficial to improve the electrical transmission performance of the electrochemical device.
[0015] In some embodiments of the present application, the conductive carbon layer includes conductive carbon and a binder, the conductive carbon includes at least one of conductive carbon black, carbon nanotubes or conductive graphite, and the binder includes at least one of polyvinylidene fluoride, styrene-butadiene rubber or acrylate; the mass percentage of the conductive carbon in the conductive carbon layer is W1%, 50≤W1≤95. By regulating the mass percentage of the conductive carbon within the above range, the obtained conductive carbon layer has good conductivity, and has strong adhesion to the substrate and is not easy to fall off.
[0016] In some embodiments of the present application, the thickness L1 of the conductive layer is 0.1 μm to 5 μm. By adjusting the thickness of the conductive layer within the above range, the conductive layer has a suitable thickness, the transmission path of lithium ions is shorter, and it is beneficial to improve the rate performance of the secondary battery.
[0017] In some embodiments of the present application, the composite current collector satisfies at least one of the following characteristics:
[0018] (a) the porosity T1 of the conductive layer is 10% to 75%;
[0019] (b) the thickness L3 of the composite current collector is 2.5 μm to 20 μm, and the thickness L2 of the substrate is 2 μm to 10 μm;
[0020] (c) the porosity T3 of the composite current collector is 5% to 80%;
[0021] (d) The porosity T of the porous polymer membrane 21 20% to 90%;
[0022] (e) The porosity T of the polymer solid electrolyte membrane or the composite solid electrolyte membrane 22 0% to 60%;
[0023] (f) The electronic conductivity of the composite current collector is σ e , 10 -8 S / m≤σ e ≤10 8 S / m.
[0024] The composite current collector satisfies at least one of the above characteristics, which is beneficial to improving the non-uniformity of the charge state of the entire negative electrode material layer, and further beneficial to improving the rate performance of the electrochemical device.
[0025] In some embodiments of the present application, the composite current collector satisfies at least one of the following characteristics:
[0026] (a) the thickness L3 of the composite current collector is 4 μm to 16 μm;
[0027] (b) The electronic conductivity of the composite current collector is σ e , 10 -3 S / m≤σ e ≤10 7 S / m.
[0028] The composite current collector satisfies at least one of the above characteristics, which is beneficial to improving the non-uniformity of the charge state of the entire negative electrode material layer, and further beneficial to improving the rate performance of the electrochemical device.
[0029] In some embodiments of the present application, the electrochemical device satisfies one of the following features:
[0030] (a) the electrode sheet is a negative electrode sheet, the negative electrode material layer is located on at least one surface of the composite current collector, the electrochemical device further comprises a positive electrode sheet, the positive electrode sheet comprises a positive current collector and a positive electrode material layer located on at least one surface of the positive current collector; a separator is included between the negative electrode material layer and the positive electrode material layer, the positive current collector is selected from metal foil, and the material of the metal foil is selected from aluminum, nickel or silver;
[0031] (b) the electrode sheet is a negative electrode sheet, the negative electrode material layer is located on one surface of the composite current collector, the electrochemical device further comprises a positive electrode sheet, the positive electrode sheet comprises a composite current collector and a positive electrode material layer located on one surface of the composite current collector, the positive electrode material layer is adjacent to a surface of the negative electrode sheet away from the negative electrode material layer, and the negative electrode material layer is adjacent to a surface of the positive electrode sheet away from the positive electrode material layer;
[0032] (c) The electrode sheet is a composite electrode sheet, and the composite electrode sheet further includes a negative electrode material layer. The positive electrode material layer is located on one surface of the composite current collector, and the negative electrode material layer is located on the other surface of the composite current collector.
[0033] The electrochemical device satisfies one of the above characteristics, the charge state uniformity of the entire negative electrode material layer is high, and the electrochemical device has good rate performance.
[0034] The second aspect of the present application provides an electronic device, which includes the electrochemical device in any of the above embodiments. Therefore, the electronic device provided by the present application has good performance.
[0035] Beneficial effects of this application:
[0036] The present application provides an electrochemical device and an electronic device, wherein the electrochemical device comprises an electrode piece, the electrode piece comprises a composite current collector and a negative electrode material layer located on the surface of the composite current collector, the XRD spectrum of the negative electrode material layer has a characteristic peak intensity of I1 at 23.5° to 24.5°, and a characteristic peak intensity of I2 at 24.5° to 25.5°; the thickness of the negative electrode material layer is Lμm, and along the thickness direction of the negative electrode material layer, the distance from any point in the negative electrode material layer to the negative electrode current collector is Zμm, and at Z=0.5L±0.1L, I1 / I2 reaches a minimum value; the ionic conductivity σ of the composite current collector is ion For 10 -4 S / cm≤σ ion ≤10 -1 The composite current collector has good lithium ion conductivity, and bidirectional lithium ion transmission can be achieved inside the negative electrode material layer, which is beneficial to improving the overall charge state non-uniformity of the negative electrode material layer, and further beneficial to improving the rate performance of the electrochemical device.
[0037] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0039] Figure 1 A schematic diagram of a partial structure of an electrochemical device in one embodiment of the present application;
[0040] Figure 2 A schematic diagram of a partial structure of an electrochemical device in another embodiment of the present application;
[0041] Figure 3 A schematic diagram of a partial structure of an electrochemical device in another embodiment of the present application;
[0042] Figure 4It is a test chart of the value of I1 / I2 of the negative electrode material layer in Example 1;
[0043] Figure 5 This is a test chart of the value of I1 / I2 of the negative electrode material layer in Comparative Example 1. DETAILED DESCRIPTION
[0044] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0045] It should be noted that in the specific implementation of the present application, lithium-ion batteries are used as an example of electrochemical devices to explain the present application, but the electrochemical devices of the present application are not limited to lithium-ion batteries. The specific technical solution is as follows:
[0046] The first aspect of the present application provides an electrochemical device, which includes a pole piece, the pole piece includes a composite current collector and a negative electrode material layer located on the surface of the composite current collector, the XRD spectrum of the negative electrode material layer has a characteristic peak intensity of I1 at 23.5° to 24.5°, and a characteristic peak intensity of I2 at 24.5° to 25.5°; the thickness of the negative electrode material layer is Lμm, and along the thickness direction of the negative electrode material layer, the distance from any point in the negative electrode material layer to the negative electrode current collector is Zμm, and at Z=0.5L±0.1L, I1 / I2 reaches a minimum value; the ionic conductivity σ of the composite current collector is ion For 10 -4 S / cm≤σ ion ≤10 -1 S / cm. For example, σ ion It can be 1.1×10 -4 S / cm, 5×10 -4 S / cm, 10 -3 S / cm, 5×10 -3 S / cm, 10 -2 S / cm, 5×10 -2 S / cm, 0.1S / cm or a range consisting of any two values therebetween.
[0047] The ionic conductivity of the composite current collector in the electrode sheet of the present application is within the above range, indicating that the composite current collector has good ionic conductivity and can be used to conduct active ions in electrochemical devices, such as lithium ions. Therefore, during the charging process of the electrochemical device, the transmission direction of lithium ions on the negative electrode material layer is in two directions. Specifically, lithium ions can be transmitted from any point in the negative electrode material layer to the side of the negative electrode material layer close to the composite current collector, and at the same time, they can be transmitted to the side of the negative electrode material layer away from the composite current collector, thereby realizing the bidirectional transmission of lithium ions. Compared with unidirectional lithium ion transmission, bidirectional transmission is conducive to improving the overall non-uniformity of the charge state of the negative electrode material layer, and thus is conducive to improving the rate performance of the electrochemical device.
[0048] At the negative electrode material layer Z = 0.5L ± 0.1L, that is, the middle area of the negative electrode material layer along the thickness direction, since lithium ions in the negative electrode material layer can achieve bidirectional transmission, during the transmission process, the middle area of the negative electrode material is the farthest from the two opposite sides of the negative electrode material layer along the thickness direction. The lithium ions in the middle area are preferentially transmitted to the two sides of the negative electrode material layer. Therefore, in the middle area of the negative electrode material layer, its state of charge is the lowest. The value of I1 / I2 can be used to characterize the amount of lithium embedded in the negative electrode active material in the negative electrode material layer. The greater the amount of lithium embedded, the lower the state of charge. Therefore, at Z = 0.5L ± 0.1L, I1 / I2 reaches the minimum value, which further illustrates that lithium ions achieve bidirectional transmission in the negative electrode material layer.
[0049] In some embodiments of the present application, at Z = 0.5L ± 0.1L, 10 ≤ I1 / I2 ≤ 30. For example, at Z = 0.5L ± 0.1L, I1 / I2 can be 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30 or a range consisting of any two values therebetween. During the charging process of an electrochemical device, the charge rate generally affects the state of charge of the negative electrode material layer. When the charge rate is 0.5C to 5C, at the negative electrode material layer Z = 0.5L ± 0.1L, 10 ≤ I1 / I2 ≤ 30. The greater the charge rate, the smaller the value of I1 / I2, and vice versa. For example, when the charging rate is 0.5C, 20≤I1 / I2≤30; when the charging rate is 1C, 15≤I1 / I2≤28; when the charging rate is 3C, 12≤I1 / I2≤25; when the charging rate is 5C, 10≤I1 / I2≤23.
[0050] In some embodiments of the present application, when the charge rate is 5C, along the thickness direction of the negative electrode material layer, the difference X between the maximum and minimum values of I1 / I2 in the negative electrode material layer is less than or equal to 30. For example, the difference X can be 5, 7, 10, 12, 15, 17, 20, 22, 25, 27, 30, or a range consisting of any two values therebetween. The difference X is within the above range, indicating that the uniformity of the overall state of charge of the negative electrode material layer is high, which is beneficial to improving the rate performance of the electrochemical device.
[0051] In some embodiments of the present application, the thickness H1 of the negative electrode material layer is 30 μm to 180 μm. In some embodiments of the present application, the thickness of the negative electrode material layer is 40 μm to 120 μm. For example, the thickness H1 of the negative electrode material layer can be 20 μm, 40 μm, 50 μm, 75 μm, 100 μm, 125 μm, 150 μm, 175 μm, 200 μm, 225 μm, 250 μm, 275 μm, 300 μm or a range consisting of any two values therebetween. By regulating the thickness of the negative electrode material layer within the above range, it has a suitable thickness, which is conducive to improving the non-uniformity of the charge state of the overall negative electrode material layer.
[0052] In some embodiments of the present application, the composite current collector includes a substrate and a conductive layer located on the surface of the substrate, the substrate includes any one of a porous polymer high molecular film, a polymer solid electrolyte membrane or a composite solid electrolyte membrane, and the conductive layer is selected from a metal layer or a conductive carbon layer. The above-mentioned substrate has good lithium ion conductivity, and the arrangement of the conductive layer makes it have good conductivity, so that during the charging process of the electrochemical device, it is beneficial to improve the overall charge state non-uniformity of the negative electrode material layer, and further to improve the rate performance of the electrochemical device.
[0053] In some embodiments of the present application, the substrate includes a porous polymer film. In some embodiments of the present application, the porous polymer film includes a polymer. In some embodiments of the present application, the polymer includes at least one of polypropylene, polyethylene terephthalate, polystyrene, polyethylene, poly(p-phenylene terephthalamide), polyethylene oxide, polymethyl methacrylate, polyacrylonitrile, polyvinylidene fluoride or polyvinylidene fluoride-hexafluoroethylene. Although the above polymer does not have lithium ion conductivity, its porous polymer film has a porous structure, which provides a channel for the transmission of lithium ions, so that the composite current collector using the substrate also has good lithium ion conductivity, which is conducive to improving the overall charge state heterogeneity of the negative electrode material layer, and then is conducive to improving the rate performance of the electrochemical device. By selecting the above polymer, the composite current collector has a higher mechanical strength, which is conducive to the processing of the electrochemical device. The present application does not limit the molecular weight of the above polymer, as long as the purpose of the present application can be achieved.
[0054] In some embodiments of the present application, the porosity T of the porous polymer membrane is 21 The porosity T3 of the composite current collector is 20% to 90%, and the porosity T4 of the composite current collector is 15% to 80%. For example, the porosity T3 of the porous polymer membrane is 20% to 90%. 21 It can be 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% or a range consisting of any two values therebetween. By regulating the porosity of the porous polymer membrane within the above range, on the one hand, a channel is provided for the transmission of lithium ions to improve the overall non-uniformity of the charge state of the negative electrode material layer; on the other hand, it plays a supporting role in setting the conductive layer, so that the composite current collector has good structural stability.
[0055] In the present application, porous polymer membranes of different thicknesses and porosities can be purchased, and the porous polymer membrane of required thickness and porosity can be selected according to the thickness and porosity test method provided in the present application.
[0056] In some embodiments of the present application, the substrate includes a polymer solid electrolyte membrane. In some embodiments of the present application, the polymer solid electrolyte membrane includes a lithium salt and a high molecular polymer. In some embodiments of the present application, the lithium salt includes at least one of LiPF6, LiN(CF3SO2)2, LiN(FSO2)2, LiCF3SO3 or LiClO4, and the high molecular polymer is the above-mentioned high molecular polymer. The polymer solid electrolyte membrane includes a lithium salt and a high molecular polymer, wherein the lithium salt enables the polymer solid electrolyte membrane to have lithium ion conductivity and enable the transmission of lithium ions. By selecting the above-mentioned lithium salt, the polymer solid electrolyte membrane can have a higher ionic conductivity, improve the transmission of lithium ions, and thereby improve the rate performance of the electrochemical device.
[0057] The present application does not particularly limit the content of lithium salt and high molecular polymer in the polymer solid electrolyte membrane, as long as the purpose of the present application can be achieved. For example, the mass ratio of lithium salt to high molecular polymer can be 1:(0.25 to 5).
[0058] In some embodiments of the present application, the polymer solid electrolyte membrane has lithium ion conductivity, which can be nearly non-porous or have a porous structure. When having a porous structure, it is more conducive to achieving bidirectional transmission of lithium ions to improve the overall charge state non-uniformity of the negative electrode material layer. Specifically, the porosity T of the polymer solid electrolyte membrane is 22 The porosity T3 of the composite current collector is 0% to 60%, and the porosity T3 of the composite current collector is 5% to 50%. 22It can be 0%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or a range consisting of any two values therebetween. By adjusting the porosity of the porous polymer polymer membrane within the above range, on the one hand, the polymer solid electrolyte membrane has lithium ion conductivity, which can improve the overall charge state non-uniformity of the negative electrode material layer; on the other hand, it plays a supporting role in setting the conductive layer, so that the composite current collector has good structural stability.
[0059] In some embodiments of the present application, the substrate includes a composite solid electrolyte membrane. The composite solid electrolyte membrane includes an inorganic solid electrolyte and a high molecular polymer. In some embodiments of the present application, the inorganic solid electrolyte includes at least one of a sulfide solid electrolyte or an oxide solid electrolyte; the sulfide solid electrolyte includes (100-x1)Li2S-x1P2S5, Li 4-x2 Ge 1-x2 P x2 S4、LiPSCl 0.8 、LiPSCl 1.3 、LiPSCl 1.5 or LiPSCl 1.6 At least one of; wherein 1≤x1≤99, 0.01≤x2≤0.99; the oxide solid electrolyte includes Li 1+x3 M x Ti 2-x3 (PO4)3、Li 1.5 Z 0.5 Ge 1.5 (PO4)3、Li 7-3x4 Ga x4 La3Zr2O 12 、Li7La3Zr2O 12 , Li 6.55 Ga 0.15 La3Zr2O 12 or Li 0.34 La 0.51 TiO 2.94At least one of; wherein, M includes at least one of Al, Cr, Ga, Fe, Sc, In, Lu, Y or La, 0≤x3≤0.5, Z includes at least one of Al, Cr, Ga, Fe, Sc, In, 0.1≤x4≤0.4. The polymer in the composite solid electrolyte membrane is the above-mentioned polymer. The composite solid electrolyte membrane includes an inorganic solid electrolyte and a polymer, wherein the inorganic solid electrolyte reduces the crystallinity of the polymer, and the polymer increases the phase interface of the inorganic solid electrolyte material, and the two act synergistically to improve the transmission of lithium ions. By selecting the above-mentioned inorganic solid electrolyte, the obtained composite solid electrolyte membrane has good ion transmission performance, which is beneficial to improving the rate performance of the electrochemical device.
[0060] The present application does not particularly limit the content of the inorganic solid electrolyte and the high molecular polymer in the composite solid electrolyte membrane, as long as the purpose of the present application can be achieved. For example, the mass ratio of the inorganic solid electrolyte to the high molecular polymer can be 1:(0.1 to 20).
[0061] In some embodiments of the present application, the composite solid electrolyte membrane has lithium ion conductivity, which can be nearly non-porous or have a porous structure. When having a porous structure, it is more conducive to achieving bidirectional transmission of lithium ions to improve the overall non-uniformity of the charge state of the negative electrode material layer. Specifically, the porosity T of the composite solid electrolyte membrane is 22 The porosity T3 of the composite current collector is 0% to 60%, and the porosity T4 of the composite current collector is 5% to 55%. 22 It can be 0%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or a range consisting of any two values therebetween. By adjusting the porosity of the composite solid electrolyte membrane within the above range, on the one hand, the polymer composite solid electrolyte membrane has lithium ion conductivity, which can improve the overall non-uniformity of the charge state of the negative electrode material layer; on the other hand, it plays a supporting role in setting the conductive layer, so that the composite current collector has good structural stability.
[0062] In some embodiments of the present application, the thickness L2 of the substrate is 2 μm to 10 μm; for example, the thickness L2 of the substrate can be 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or a range consisting of any two values therebetween. By regulating the thickness L2 of the substrate within the above range, the obtained composite current collector has suitable mechanical strength and a short transmission path for lithium ions, which is conducive to improving the rate performance of the solid-state secondary battery.
[0063] In some embodiments of the present application, the conductive layer is located on one surface of the substrate. In another embodiment, the conductive layer is located on both surfaces of the substrate, that is, the composite current collector comprises two conductive layers, which may be the same or different. The surface of the above-mentioned substrate refers to the two surfaces of the substrate that are opposite to each other along its thickness direction, and the conductive layer may be arranged in a partial area of the substrate surface or in the entire area of the substrate surface, which may be selected according to actual conditions, as long as the purpose of the present application can be achieved.
[0064] In some embodiments of the present application, the conductive layer is selected from a metal layer, and the material of the metal layer is selected from any one of aluminum, copper, nickel or silver. The metal layer has good electrical conductivity, and the obtained composite current collector also has good electrical conductivity, which is beneficial to improving the electrical transmission performance of the electrochemical device.
[0065] In some embodiments of the present application, the conductive layer is selected from a conductive carbon layer, and the conductive carbon layer includes conductive carbon and a binder. The conductive carbon includes at least one of conductive carbon black, carbon nanotubes or conductive graphite, and the binder includes at least one of polyvinylidene fluoride, styrene butadiene rubber or acrylate. The conductive carbon layer has good conductive stability, is not easily oxidized and corroded during the charge and discharge cycle of the electrochemical device, and has high safety. At the same time, the interface impedance between it and the positive electrode material layer or the negative electrode material is small, which is beneficial to improve the expansion rate and capacity retention rate during the cycle of the electrochemical device. In addition, while having high electronic conductivity, the conductive carbon layer also has a certain elasticity, which can buffer the capacity attenuation caused by the volume expansion of the pole piece, thereby helping to improve the rate performance of the electrochemical device. The mass percentage of conductive carbon in the conductive carbon layer is W1%, 50≤W1≤95, and the mass percentage of the binder W2 is 5% to 50%. For example, W1 can be 50, 55, 60, 65, 70, 75, 80, 85, 90, 95 or a range consisting of any two values therebetween. For example, the mass percentage content W2 of the binder can be 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50% or a range consisting of any two values therebetween. By adjusting the mass percentage content of the conductive carbon and the binder within the above range, the obtained conductive carbon layer has good conductivity, and has strong adhesion to the substrate and is not easy to fall off.
[0066] In some embodiments of the present application, the thickness L1 of the conductive layer is 0.1 μm to 5 μm. For example, the thickness L1 of the conductive layer can be 0.1 μm, 0.5 μm, 1 μm, 1.3 μm, 1.5 μm, 1.7 μm, 2 μm, 2.3 μm, 2.5 μm, 2.7 μm, 3 μm, 3.3 μm, 3.5 μm, 3.7 μm, 4 μm, 4.3 μm, 4.5 μm, 4.7 μm, 5 μm or a range consisting of any two values therebetween. By regulating the thickness of the conductive layer within the above range, the conductive layer has a suitable thickness, and the transmission path of lithium ions is short, which is conducive to improving the rate performance of the solid-state secondary battery.
[0067] In some embodiments of the present application, the conductive layer is selected from a metal layer, and the thickness L1 of the conductive layer is 0.1 μm to 5 μm. In some embodiments of the present application, the conductive layer is selected from a conductive carbon layer, and the thickness L1 of the conductive layer is 0.1 μm to 5 μm.
[0068] In some embodiments of the present application, the porosity T1 of the conductive layer is 10% to 75%; for example, the porosity T1 of the conductive layer can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or a range consisting of any two values therebetween. By regulating the porosity of the conductive layer within the above range, a channel is provided for the transmission of lithium ions, so that the electrode can achieve bidirectional transmission of lithium ions during the charging process, so as to improve the overall non-uniformity of the state of charge of the negative electrode material layer, thereby facilitating the improvement of the rate performance of the electrochemical device.
[0069] In some embodiments of the present application, the porosity T of the porous polymer membrane is 21 is 20% to 90%, the porosity T1 of the conductive layer is 10% to 75%, 1≤T 21 / T1≤2.
[0070] In some embodiments of the present application, the porosity T of the polymer solid electrolyte membrane or the composite solid electrolyte membrane is 22 is 0% to 60%, the porosity T1 of the conductive layer is 10% to 75%, 0≤T 22 / T1≤2.
[0071] In some embodiments of the present application, the thickness L3 of the composite current collector is 2.5 μm to 20 μm, and the thickness L3 of the composite current collector is 4 μm to 16 μm. For example, the thickness L3 of the composite current collector can be 2.5 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm or a range consisting of any two values therebetween. By regulating the thickness of the composite current collector within the above range, the composite current collector has a suitable thickness, the transmission path of lithium ions is short, and it is beneficial to improve the rate performance of the solid-state secondary battery.
[0072] In some embodiments of the present application, the composite current collector includes a substrate and a conductive layer, and the thickness L3 of the composite current collector is 2.5 μm to 15 μm. In some embodiments of the present application, the composite current collector includes a substrate and two conductive layers, and the thickness L3 of the composite current collector is 2.5 μm to 20 μm.
[0073] In some embodiments of the present application, the electronic conductivity of the composite current collector is σ e , 10 -8 S / m≤σ e ≤10 8 S / m, in some embodiments of the present application, 10 -3 S / m≤σ e ≤10 7 S / m. For example, σ e Can be 10 -8 S / m, 1.1×10 -8 S / m, 10 -7 S / m, 10 -6 S / m, 10 -5 S / m, 10 -4 S / m, 10 -3 S / m, 10 -2 S / m, 10 -1 S / m, 1S / m, 10S / m, 10 2 S / m, 10 3 S / m, 10 4 S / m, 10 5 S / m, 10 6 S / m, 10 7 S / m, 9.9×10 7 S / m, 10 8S / m or a range consisting of any two values therebetween. The electronic conductivity of the composite current collector is within the above range, indicating that it has good electronic conductivity and ion conductivity. Applying it to an electrochemical device can improve the overall charge state non-uniformity of the negative electrode material layer, thereby improving the rate performance of the electrochemical device.
[0074] In some embodiments of the present application, Figure 1 As shown, the electrode sheet is a negative electrode sheet 02, and the negative electrode material layer 21 is located on one surface of the composite current collector 20. Specifically, the negative electrode material layer 21 can be located on one surface of the composite current collector 20, and the composite current collector 20 includes a substrate 202 and a conductive layer, which is recorded as the first conductive layer 202, and the first conductive layer 202 is located between the substrate 201 and the negative electrode material layer 21. The electrochemical device also includes a positive electrode sheet 01, and the positive electrode sheet 01 includes a positive electrode collector 10 and a positive electrode material layer 11 located on both surfaces of the positive electrode collector 10. A separator 04 is included between the positive electrode material layer 11 and the negative electrode material layer 21, and a separator 04 is provided between the side of the negative electrode sheet 02 where the negative electrode material layer 21 is not provided and the positive electrode sheet 01. In the above structure, the side of the negative electrode sheet where the negative electrode material layer is not provided is a surface of the substrate. In some embodiments of the present application, when the thickness of the substrate is greater than 5 μm, a separator may not be provided between the side of the negative electrode plate where the negative electrode material layer is not provided and the positive electrode plate. It is understandable that a separator may also be provided between the side of the negative electrode plate where the negative electrode material layer is not provided and the positive electrode plate to better prevent internal short circuits.
[0075] In some embodiments of the present application, the positive electrode current collector is selected from metal foil, and the material of the metal foil is selected from aluminum, nickel, copper or silver.
[0076] During the charging process of the electrochemical device, the electrochemical device has the above structure, and the lithium ions in the negative electrode material layer can be transferred to the negative electrode material layers on both sides, realizing the bidirectional transmission of lithium ions, which is beneficial to improving the overall charge state non-uniformity of the negative electrode material layer, and further beneficial to improving the rate performance of the electrochemical device.
[0077] In some embodiments of the present application, Figure 2As shown, the electrode sheet is a negative electrode sheet 02, and the negative electrode material layer 21 is located on one surface of the composite current collector 20. The composite current collector 20 includes a substrate 201 and a conductive layer, which is recorded as a first conductive layer 202, and the first conductive layer 202 is located between the substrate 201 and the negative electrode material layer 21. The electrochemical device also includes a positive electrode sheet 01, and the positive electrode sheet 01 includes a composite current collector 20 and a positive electrode material layer 11 located on one surface of the composite current collector 20, wherein the composite current collector 20 includes a substrate 201 and a conductive layer, which is recorded as a second conductive layer 203. The positive electrode material layer 11 is adjacent to the surface of the negative electrode sheet 02 away from the negative electrode material layer 21, and the negative electrode material layer 21 is adjacent to the surface of the positive electrode sheet 01 away from the positive electrode material layer 11. In the present application, the first conductive layer 202 and the second conductive layer 203 may be the same or different. Preferably, the first conductive layer 202 and the second conductive layer 203 are different. Specifically, Figure 2 The first conductive layer 202 and the second conductive layer 203 in the embodiment are different conductive layers.
[0078] During the charging process of the electrochemical device, the lithium ions in the negative electrode material layer can be transferred to the negative electrode material layers on both sides to achieve bidirectional transmission of lithium ions, which is beneficial to improve the overall non-uniformity of the charge state of the negative electrode material layer, and thus is beneficial to improve the rate performance of the electrochemical device. In the above structure, the side of the composite current collector in the positive electrode sheet and the negative electrode sheet where the positive electrode material layer or the negative electrode material layer is not provided is a surface of the substrate. In some embodiments of the present application, when the thickness of the substrate is greater than 5μm, no diaphragm may be provided between the positive electrode sheet and the negative electrode sheet. It is understandable that a diaphragm may also be provided between the positive electrode sheet and the negative electrode sheet to prevent internal short circuits.
[0079] In some embodiments of the present application, Figure 3 As shown, the electrode sheet is a composite electrode sheet 03, which includes a positive electrode material layer 11, a negative electrode material layer 21 and a composite current collector 20. The positive electrode material layer 11 is located on one surface of the composite current collector 20, and the negative electrode material layer 21 is located on the other surface of the composite current collector 20. A separator 04 is provided between two adjacent composite electrode sheets 03. The composite current collector 20 includes a substrate 201, a first conductive layer 202 and a second conductive layer 203. The first conductive layer 202 is located between the substrate 201 and the negative electrode material layer 21, and the second conductive layer 203 is located between the substrate 201 and the positive electrode material layer 11. The composite electrode sheet is a bipolar electrode sheet. During the charging process of the electrochemical device, the lithium ions in the negative electrode material layer can be transferred to the negative electrode material layers on both sides to realize the bidirectional transmission of lithium ions, which is beneficial to improve the non-uniformity of the overall state of charge of the negative electrode material layer, and further to improve the rate performance of the electrochemical device.
[0080] In the present application, the first conductive layer and the second conductive layer in the composite pole piece may be the same or different. Preferably, the first conductive layer and the second conductive layer are different.
[0081] In some embodiments of the present application, the first conductive layer and the second conductive layer are each independently selected from metal layers, the first conductive layer is a copper metal layer, and the second metal layer is an aluminum metal layer.
[0082] In some embodiments of the present application, the first conductive layer and the second conductive layer are each independently selected from a conductive carbon layer. The mass percentage of the conductive carbon material in the first conductive layer is X1, and the mass percentage of the conductive carbon material in the second conductive layer is X2, 1≤X1 / X2≤2. For example, X1 / X2 can be 1.01, 1.1, 1.2, 1.4, 1.6, 1.8, 2 or a range consisting of any two values therein. The conductivity of the negative electrode material layer is generally stronger than that of the positive electrode material layer, so that the content of the conductive carbon material in the first conductive layer is greater than the content of the conductive carbon material in the second conductive layer, which can make the composite electrode sheet have good conductivity as a whole. In some embodiments of the present application, 60%≤X1≤95%, 50%≤X2≤95%.
[0083] In some embodiments of the present application, the thickness L of the first conductive layer is 11 Less than or equal to the thickness L of the second conductive layer 12 , 1≤L 12 / L 11 ≤5. In some embodiments of the present application, 0.1 μm ≤ L 11 ≤5μm, 0.2μm≤L 12 ≤5μm.
[0084] In some embodiments of the present application, the porosity T of the first conductive layer is 11 For example, T 11 It may be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or a range consisting of any two values therebetween. In some embodiments of the present application, the porosity T of the second conductive layer is 12 For example, T 12 It can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75% or a range consisting of any two values therebetween.
[0085] The present application has no particular restrictions on the preparation method of the polymer solid electrolyte membrane, as long as the purpose of the present application can be achieved. For example, the preparation method of the polymer solid electrolyte membrane may include but is not limited to the following steps: mixing lithium salt, high-density polymer and solvent, and dispersing them evenly to obtain a mixed solution. The mixed solution is scraped on a substrate, dried and separated from the substrate to obtain a polymer solid electrolyte membrane. Among them, the solid content of the mixed solution can be 5% to 75%. The present application does not limit the above-mentioned solvent, as long as the purpose of the present application can be achieved. For example, the above-mentioned solvent may include but is not limited to at least one of N,N-dimethylformamide (DMF), isopropyl alcohol (IPA) or N-methylpyrrolidone (NMP). The present application has no particular restrictions on the base film, as long as the purpose of the present application can be achieved. For example, the base film may be a polyethylene terephthalate (PET) base film.
[0086] The present application has no particular restrictions on the preparation method of the composite solid electrolyte membrane, as long as the purpose of the present application can be achieved. For example, the preparation method of the composite solid electrolyte membrane may include but is not limited to the following steps: mixing a polymer, an inorganic solid electrolyte and a solvent, and dispersing them evenly to obtain a mixed solution. The mixed solution is scraped on a substrate, dried and separated from the substrate to obtain a composite solid electrolyte membrane. Among them, the solid content of the mixed solution can be 5% to 75%. The present application does not limit the above-mentioned solvent, as long as the purpose of the present application can be achieved. For example, the above-mentioned solvent may include but is not limited to at least one of N,N-dimethylformamide (DMF), isopropyl alcohol (IPA) or N-methylpyrrolidone (NMP). The present application has no particular restrictions on the temperature and vacuum degree of the above-mentioned drying, as long as the purpose of the present application can be achieved. For example, the drying temperature can be 60°C to 120°C and the vacuum degree can be 0.01MPa to 0.06MPa.
[0087] The present application does not particularly limit the method for regulating the thickness of the polymer solid electrolyte membrane or the composite solid electrolyte membrane, as long as the purpose of the present application can be achieved. For example, it can be regulated by regulating the solid content of the mixed solution and the amount of the mixed solution scraped. Exemplarily, if the solid content of the mixed solution is constant, the amount of the mixed solution scraped increases, and the thickness of the polymer solid electrolyte membrane or the composite solid electrolyte membrane increases, otherwise it decreases; if the amount of the mixed solution scraped is constant, the solid content of the mixed solution increases, and the thickness of the polymer solid electrolyte membrane or the composite solid electrolyte membrane increases, otherwise it decreases.
[0088] The present application does not particularly limit the method for regulating the porosity of the polymer solid electrolyte membrane or the composite solid electrolyte membrane, as long as the purpose of the present application can be achieved. For example, it can be regulated by regulating the drying temperature and vacuum degree during the preparation process. Exemplarily, during the preparation process, the coating thickness is constant, and the porosity of the polymer solid electrolyte membrane or the composite solid electrolyte membrane increases when the drying temperature or the vacuum degree is increased, and vice versa.
[0089] The conductive layer is a metal layer, and the present application has no particular restrictions on the preparation method of the composite current collector, as long as the purpose of the present application can be achieved. For example, the composite current collector includes a conductive layer, and its preparation method may include but is not limited to the following steps: a conductive layer is set on one surface of the substrate by magnetron sputtering. For another example, the composite current collector includes two conductive layers, and its preparation method may include but is not limited to the following steps: a conductive layer is set on one surface of the substrate by magnetron sputtering, and a conductive layer is set on the other surface of the substrate by magnetron sputtering. The thickness of the conductive layer is mainly regulated by the amount of metal sputtered by magnetron. As the amount of metal increases, the thickness of the conductive layer increases, and vice versa. The porosity of the conductive layer mainly depends on the metal sputtering rate per unit time of magnetron sputtering. As the metal sputtering rate increases, the thickness of the conductive layer increases, and vice versa.
[0090] The conductive layer is a conductive carbon layer. The present application has no particular restrictions on the preparation method of the composite current collector, as long as the purpose of the present application can be achieved. For example, the composite current collector includes a conductive layer, and its preparation method may include but is not limited to the following steps: uniformly mixing the conductive carbon material, the binder and the solvent to obtain a conductive carbon layer slurry; coating the conductive carbon layer slurry on one surface of the substrate, and drying to obtain a composite current collector. For another example, the composite current collector includes two conductive layers, and the preparation method of the composite current collector may include but is not limited to the following steps: uniformly mixing the conductive carbon material, the binder and the solvent to obtain a conductive carbon layer slurry; coating the conductive carbon layer slurry on one surface of the substrate, and drying; coating the conductive carbon layer slurry on the other surface of the substrate, and drying to obtain a composite current collector. Among them, the solid content of the conductive carbon layer slurry can be 0.5% to 5%. The present application does not limit the above-mentioned solvent, as long as the purpose of the present application can be achieved. For example, the above-mentioned solvent may include but is not limited to at least one of water, N-methylpyrrolidone (NMP) or N,N-dimethylformamide (DMF). It is understood that when the composite current collector includes two conductive layers, the conductive carbon materials in the two conductive layers may be the same or different, and the binders may be the same or different. The present application has no particular restrictions on the above-mentioned drying temperature and vacuum degree, as long as the purpose of the present application can be achieved. For example, the drying temperature may be 60°C to 120°C, and the vacuum degree may be 0.01MPa to 0.06MPa.
[0091] The conductive layer is a conductive carbon layer, and the thickness of the conductive layer can be regulated by regulating the solid content and coating amount of the conductive carbon layer slurry. When the solid content of the conductive carbon layer slurry is constant, the coating amount is increased, and the thickness of the conductive layer increases, otherwise it decreases; when the coating amount of the conductive carbon layer slurry is constant, the solid content is increased, and the thickness of the conductive layer increases, otherwise it decreases. The porosity of the conductive layer is related to the porosity of the substrate. At the same time, the porosity and pore size of the conductive layer can be adjusted by regulating the coating parameters of the conductive carbon layer slurry, the viscosity of the conductive carbon layer slurry, the drying temperature, etc. Specifically, the conductive carbon layer slurry can be coated in a gravure manner, and the porosity of the conductive layer can be regulated by adjusting the specifications of the gravure. When the solid content of the conductive carbon layer slurry is constant, the viscosity of the conductive carbon layer slurry can be regulated by adding a dispersant. For example, when the viscosity of the conductive carbon layer slurry increases, the porosity and pore size of the conductive layer decrease, otherwise it increases. When the solid content of the conductive carbon layer slurry is constant, the higher the drying temperature and the higher the vacuum degree, the greater the porosity of the conductive carbon layer, otherwise it decreases.
[0092] The above-mentioned electrode sheet is a negative electrode sheet, and the negative electrode material layer is located on one surface of the composite current collector. The composite current collector includes a substrate and a conductive layer, and the conductive layer is located between the substrate and the negative electrode material layer. The present application has no particular restrictions on the method for preparing the negative electrode sheet, as long as the purpose of the present application can be achieved. For example, the method for preparing the negative electrode sheet may include but is not limited to the following steps: preparing a negative electrode material layer slurry, coating the negative electrode material layer slurry on one surface of the composite current collector, and drying to obtain a negative electrode sheet. It is understandable that by repeating the above operation on the other surface of the composite current collector, a positive electrode sheet coated with a negative electrode material layer on both sides can be obtained. When the positive electrode sheet also contains a composite current collector, its preparation method can refer to the above-mentioned method for preparing the negative electrode sheet.
[0093] The composite electrode sheet includes a positive electrode material layer and a negative electrode material layer, the positive electrode material layer is located on one surface of the composite current collector, and the negative electrode material layer is located on the other surface of the composite current collector. The present application has no particular restrictions on the preparation method of the composite electrode sheet, as long as the purpose of the present application can be achieved. For example, the preparation method of the composite electrode sheet may include but is not limited to the following steps: preparing a positive electrode material layer slurry, preparing a negative electrode slurry material layer; coating the positive electrode material layer slurry on one surface of the composite current collector, drying, to obtain a composite current collector provided with a positive electrode material layer; coating the negative electrode material layer slurry on the other surface of the composite current collector, drying, to obtain a composite electrode sheet. The thickness of the negative electrode material layer can be regulated by regulating the solid content and coating amount of the negative electrode material layer slurry. If the solid content of the negative electrode material layer slurry is constant, increasing the coating amount will increase the thickness of the negative electrode material layer, and vice versa; if the coating amount of the negative electrode material layer slurry is constant, increasing the solid content will increase the thickness of the negative electrode material layer, and vice versa. The thickness of the positive electrode material layer can be regulated by referring to the regulation method of the thickness of the negative electrode material layer.
[0094] In some embodiments of the present application, the negative electrode material layer includes a negative electrode active material, the negative electrode active material includes at least one of graphite, a graphite silicon-carbon composite material, a graphite hard carbon composite material, or a graphite soft carbon composite material, and hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 or Li-Al alloy. The graphite may include but is not limited to at least one of natural graphite, artificial graphite or mesophase carbon microspheres. The negative electrode active material has a high specific capacity, which is beneficial to improve the energy density of the electrochemical device and improve the cycle performance.
[0095] In some embodiments of the present application, the negative electrode material layer may also include a negative electrode conductive agent and a negative electrode binder. The present application does not particularly limit the types of negative electrode conductive agents and negative electrode binders, as long as the purpose of the present application can be achieved. For example, the negative electrode conductive agent may include but is not limited to at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers, and the conductive carbon black may include but is not limited to at least one of acetylene black or Ketjen black. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers. Specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymers may include but are not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. The negative electrode binder may include, but is not limited to, at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyimide, polyamide-imide, styrene-butadiene rubber, or polyvinylidene fluoride. The present application does not particularly limit the mass ratio of the negative electrode active material, the negative electrode conductive agent, and the negative electrode binder in the negative electrode material layer. Those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.
[0096] The present application has no particular limitation on the thickness of the negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of a single layer of negative electrode material layer can be 30 μm to 180 μm.
[0097] In some embodiments of the present application, the positive electrode material layer includes a positive electrode active material, which may include but is not limited to at least one of lithium nickel cobalt manganese oxide (e.g., NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium iron manganese phosphate, or lithium titanate.
[0098] The positive electrode material layer may also include a positive electrode conductor and a positive electrode binder. The present application has no particular restrictions on the types of the positive electrode conductor and the positive electrode binder, as long as the purpose of the present application can be achieved. For example, it may be at least one of the above-mentioned negative electrode conductor and the above-mentioned negative electrode binder. The present application has no particular restrictions on the mass ratio of the positive electrode active material, the positive electrode conductor, and the positive electrode binder in the positive electrode material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved.
[0099] The present application has no particular restrictions on the thickness of the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of a single-layer positive electrode material layer can be 30 μm to 300 μm. The present application has no particular restrictions on the thickness of the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector is 4 μm to 15 μm.
[0100] In the present application, the electrochemical device also includes an electrolyte solution including an electrolyte salt and a non-aqueous solvent.
[0101] The present application has no particular restrictions on lithium salts, as long as the purpose of the present application can be achieved. For example, the electrolyte salt may include but is not limited to at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalatoborate) (C4BLiO8, abbreviated as LiBOB) or lithium difluoroborate. The present application has no particular restrictions on the content of the electrolyte salt in the electrolyte, as long as the purpose of the present application can be achieved.
[0102] The present application has no particular restrictions on non-aqueous solvents, as long as the purpose of the present application can be achieved, for example, non-aqueous solvents may include but are not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents. The above-mentioned carbonate compounds may include but are not limited to at least one of linear carbonate compounds, cyclic carbonate compounds or fluorinated carbonate compounds. The above-mentioned linear carbonate compounds may include but are not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or ethyl methyl carbonate (MEC). The above-mentioned cyclic carbonate may include but are not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The fluorinated carbonate compound may include, but is not limited to, at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include, but is not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate. The present application has no particular restrictions on the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved.
[0103] The present application has no particular restrictions on the diaphragm, as long as the purpose of the present application can be achieved. For example, the material of the diaphragm may include, but is not limited to, polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (e.g., polyethylene terephthalate (PET) films), cellulose, polyimide (PI), polyamide (PA), spandex or aramid. The type of diaphragm may include at least one of a woven membrane, a nonwoven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.
[0104] In some embodiments of the present application, the diaphragm may include a substrate layer and a surface treatment layer. The substrate layer may be a nonwoven fabric, a film or a composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used.
[0105] Optionally, a surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.
[0106] In some embodiments of the present application, the inorganic layer includes inorganic particles and a binder. The present application is not particularly limited to inorganic particles, such as inorganic particles can include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application is not particularly limited to binders, such as binders can be at least one of the above-mentioned binders. In some embodiments of the present application, the polymer layer includes polymers, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymers, polyacrylic acid, polyacrylates, polyvinyl pyrrolidone, polyvinyl ether or polyvinylidene fluoride or poly (vinylidene fluoride-hexafluoropropylene).
[0107] In the present application, there is no particular limitation on the thickness of the separator as long as the purpose of the present application can be achieved. For example, the thickness of the separator may be 3 μm to 30 μm.
[0108] The electrochemical device also includes a housing for accommodating a positive electrode plate, a diaphragm, a negative electrode plate and an electrolyte, as well as other components known in the field of electrochemical devices, and this application does not limit the above-mentioned other components. This application does not particularly limit the housing, and it can be a housing known in the art, as long as the purpose of this application can be achieved. For example, the housing can be a hard shell housing or a flexible shell. The material of the hard shell housing can be metal, and this application does not limit the type of metal, and a metal hard shell housing known in the art can be used, as long as the purpose of this application can be achieved. The flexible housing can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.
[0109] The preparation process of the electrochemical device of the present application is well known to those skilled in the art, and the present application has no particular limitations. For example, the electrochemical device includes a positive electrode sheet, a negative electrode sheet and a separator, and its preparation process may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly of a wound structure, placing the electrode assembly in a shell, injecting an electrolyte into the shell and sealing it to obtain an electrochemical device. Alternatively, stack the positive electrode sheet, the separator and the negative electrode sheet in order, and then fix the four corners of the entire stacked structure with tape to obtain an electrode assembly of a stacked structure, placing the electrode assembly in a shell, injecting an electrolyte into the shell and sealing it to obtain an electrochemical device. Among them, the number of layers of the positive electrode sheet, the negative electrode sheet and the separator can be selected according to actual conditions, and the present application does not limit this.
[0110] For example, an electrochemical device includes a composite electrode and a diaphragm, and its preparation process may include but is not limited to the following steps: stacking the composite electrode and the diaphragm in order, and winding, folding, etc. as needed to obtain an electrode assembly with a wound structure, placing the electrode assembly in a shell, injecting an electrolyte into the shell and sealing it to obtain an electrochemical device. Alternatively, stacking the composite electrode and the diaphragm in order, and then fixing the four corners of the entire laminated structure with tape to obtain an electrode assembly with a laminated structure, placing the electrode assembly in a shell, injecting an electrolyte into the shell and sealing it to obtain an electrochemical device. Among them, the number of layers of the composite electrode and the diaphragm can be selected according to actual conditions, and this application does not limit this.
[0111] Furthermore, as required, an overcurrent prevention element, a guide plate, etc. may be placed in the housing to prevent pressure rise and overcharge and discharge inside the electrochemical device.
[0112] In some embodiments of the present application, the electrochemical device of the present application may include but is not limited to: lithium metal secondary battery, lithium ion secondary battery (lithium ion battery), lithium polymer secondary battery or lithium ion polymer secondary battery, etc. In some embodiments of the present application, the electrochemical device includes a lithium ion battery.
[0113] The second aspect of the present application provides an electronic device, which includes the electrochemical device in any of the above embodiments. Therefore, the electronic device provided by the present application has good performance.
[0114] The present application does not particularly limit the type of electronic device, and it can be used for any electronic device known in the prior art. In some embodiments of the present application, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0115] Example
[0116] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0117] Test methods and equipment:
[0118] The voltage range shall be based on the voltage range marked on the outer packaging of the battery. For example, when the voltage range marked on the battery is 3.0V to 4.5V, the charging cut-off voltage is 4.5V and the discharging cut-off voltage is 3.0V.
[0119] After the lithium-ion battery is charged with a 1C constant current to a cut-off voltage of 4.5V, it is then charged with a 4.5V constant voltage to a cut-off current of 0.05C, which is fully charged. The fully charged lithium-ion battery is disassembled in an argon atmosphere, and the positive electrode is rinsed with diethyl carbonate (DEC) solvent for 1 minute. After rinsing, the positive electrode is dried and then attached to the micro-area X-ray diffractometer (XRD) test bench, where the minimum spot of the micro-area XRD can reach 5μm. The negative anode electrode is obtained by XRD detection at different positions in the thickness direction through a microscope. The specific test positions are 5μm, 0.25H+2, 0.5H, 0.75H-2, and H-5μm from the current collector, where H is the thickness of the current collector, and I1 and I2 at different positions in the thickness direction are obtained, and then the values of I1 / I2 at different positions are obtained, and the distance-I1 / I2 curve at 1C is drawn. Then change the charging current to 3C and 5C in turn, and you can get the curve of the distance from the current collector - I1 / I2 at 3C and the curve of the distance from the current collector - I1 / I2 at 5C. The charge state in the thickness direction of the negative electrode material layer is analyzed based on I1 / I2. In this application, the position where the center of the light spot is 5μm away from the edge of the negative electrode material layer is defined as the edge position of the negative electrode pole piece detection. The relative humidity of the lithium-ion battery test environment is less than 0.1%, and the dew point temperature is lower than -50°C. Among them, I1 is the characteristic peak intensity of the XRD spectrum of the negative electrode material layer at 23.5° to 24.5°, and I2 is the characteristic peak intensity of the XRD spectrum of the negative electrode material layer at 24.5° to 25.5°; the above-mentioned current collector can be the composite current collector in the embodiment and the negative electrode current collector in Comparative Example 1.
[0120] The values of I1 / I2 in Table 1 and Table 2 are all measured at a charging rate of 5C.
[0121] Rate performance test:
[0122] The kinetic improvement effect on lithium-ion batteries is characterized by testing the capacity retention rate at different rates.
[0123] The voltage range shall be based on the voltage range marked on the outer packaging of the battery. For example, when the voltage range marked on the battery is 3.0V to 4.5V, the charging cut-off voltage is 4.5V and the discharging cut-off voltage is 3.0V.
[0124] At 25°C, the lithium-ion battery is charged to 4.5V at 1C, then charged at 4.5V at constant voltage to a current of 0.05C, left to stand for 5 minutes, and discharged at a constant current of 0.2C to a voltage of 3.0V. The discharge capacity of the lithium-ion battery at this time is recorded as C0; then the lithium-ion battery is charged to 4.5V at 1C, then charged at 4.5V at constant voltage to a current of 0.05C, left to stand for 5 minutes, and discharged at a constant current of 0.5C to a voltage of 3.0V; then the lithium-ion battery is charged to 4.5V at 1C, then charged at 4.5V at constant voltage to a current of 0.05C, left to stand for 5 minutes, and discharged at a constant current of 1C to a voltage of 3.0V; then the lithium-ion battery is charged to 4.5V at 1C, then charged at 4.5V at constant voltage to a current of 0. 05C, let it stand for 5min, and discharge it at a constant current of 2C to a voltage of 3.0V; then charge the lithium-ion battery to 4.5V at 1C, and then charge it at a constant voltage at 4.5V to a current of 0.05C, let it stand for 5min, and discharge it at a constant current of 3C to a voltage of 3.0V. The discharge capacity of the lithium-ion battery at this time is recorded as C4; then charge the lithium-ion battery to 4.5V at 1C, and then charge it at a constant voltage at 4.5V to a current of 0.05C, let it stand for 5min, and discharge it at a constant current of 4C to a voltage of 3.0V; then charge the lithium-ion battery to 4.5V at 1C, and then charge it at a constant voltage at 4.5V to a current of 0.05C, let it stand for 5min, and discharge it at a constant current of 5C to a voltage of 3.0V. The discharge capacity of the lithium-ion battery at this time is recorded as C6;
[0125] 3C discharge capacity retention rate (%) = C4 / C0×100%;
[0126] 5C discharge capacity retention rate (%) = C6 / C0×100%.
[0127] Acquisition of composite current collector samples and substrate samples:
[0128] The voltage range shall be based on the voltage range marked on the outer packaging of the battery. For example, when the voltage range marked on the battery is 3.0V to 4.5V, the charging cut-off voltage is 4.5V and the discharging cut-off voltage is 3.0V.
[0129] The lithium-ion battery is discharged at a constant current of 0.5C to a discharge cut-off voltage of 3V, the lithium-ion battery is disassembled, the pole piece is taken out, the positive electrode material layer and / or the negative electrode material layer on the surface is immersed in an N-methylpyrrolidone (NMP) solution at room temperature for 30 minutes, and then the composite pole piece is wiped with dust-free paper to remove the positive electrode material layer and / or the negative electrode material layer on the surface of the pole piece, and then ultrasonically cleaned in an NMP solution for 30 minutes, with an ultrasonic frequency of 80Hz, to obtain a composite current collector. The above-mentioned pole piece can be a positive pole piece, a negative pole piece or a composite pole piece containing a composite current collector.
[0130] The composite current collector is cleaned by plasma to remove the conductive layer, thereby obtaining a substrate, wherein the conductive layer includes a first conductive layer and / or a second conductive layer.
[0131] Unless otherwise specified, the following test methods all use the composite current collector and substrate obtained above.
[0132] Thickness test:
[0133] The cross section of the composite current collector is polished by using an argon ion polishing technique, and then a photograph of the cross section is taken by using a scanning electron microscope. The thickness L2 of the substrate can be measured based on the photograph of the cross section.
[0134] The cross-section of the composite current collector is photographed by X-ray tomography, and the thickness L of the first conductive layer can be measured based on the cross-section photograph. 11 and the thickness L of the second conductive layer 12 .
[0135] When measuring thickness, measure 10 locations randomly and take the average value as the final result.
[0136] Porosity test of substrate, first conductive layer and second conductive layer:
[0137] Porosity = (apparent volume of sample - true volume of sample) / apparent volume of sample;
[0138] Apparent volume of the sample: Use a solid mold (5 cm × 10 cm) with an area of S1 to punch out and measure the thickness h of the sample to obtain the apparent volume V of the sample. S =S1×h;
[0139] True volume of the sample: The test principle is to use the Archimedean principle of gas displacement through the gas displacement method, and use the Bohr law (PV=nRT) of inert gas with small molecular diameter under certain conditions to accurately measure the true volume of the sample being tested. Take the punched sample above, place it in the true density tester, close the test system, and introduce helium according to the procedure. By detecting the gas pressure in the sample chamber and the expansion chamber, the true volume is calculated according to Bohr's law:
[0140] (1)P1(V cell -V samp )=n c RT a ;
[0141] (2)P a V exp =n e RT a ;
[0142] When the valve is opened, the pressure drops to the middle value P2, and the mass conservation law becomes: (3) P2 (V cell-V samp +V exp =n c RT a +n e RT a ;
[0143] Then the actual volume of the sample is: (4) V samp =(V cell -V exp )×(P2-P a ) / (P1-P2);
[0144] Among them, n c is the molar mass of the gas in the sample cup; n e is the molar mass of the gas in the expanding gas; R is the ideal gas constant; T a is the ambient temperature; V cell is the volume of the sample cup, V samp is the true volume of the sample; V exp is the volume of the expansion chamber; P1 is the gas pressure in the sample chamber, P2 is the equilibrium pressure after the gas diffuses in the entire system, and P a is the pressure of the gas in the expansion chamber.
[0145] The volume V0 and porosity T3 of the composite current collector, as well as the volume V1 and porosity P1 of the substrate are measured by the above method. When the substrate is a porous polymer membrane, P1 is also T 21 When the substrate is a polymer solid electrolyte membrane or a composite solid electrolyte membrane, P1, also known as T 22 .
[0146] When the composite current collector includes a substrate and a first conductive layer disposed on one surface of the substrate, the porosity of the first conductive layer P2 (%) = (T3 × V0-P1 × V1) / (V0-V1); when the composite current collector includes a substrate and a second conductive layer disposed on one surface of the substrate, the porosity of the second conductive layer P3 (%) = (T3 × V0-P1 × V1) / (V0-V1);
[0147] When the composite current collector includes a substrate, a first conductive layer, and a second conductive layer, the substrate is disposed between the first conductive layer and the second conductive layer, the volume V0 and the porosity T3 of the composite current collector are measured by the above method; the second conductive layer is then removed by plasma cleaning to obtain the substrate and the first conductive layer, and the volume V1' and the porosity T3 of the substrate and the first conductive layer are measured. 11 ; Then the porosity T of the second conductive layer 12 (%) = (T3 × V0 - T 11×V1') / (V0-V1'); then the first conductive layer is removed by plasma cleaning to obtain a substrate, and the volume V1 and porosity P1 of the substrate are measured; then the porosity T of the first conductive layer is 11 (%)=(T 11 ×V1'-P1×V1) / (V1'-V1).
[0148] Ionic conductivity test:
[0149] 1) Electrolyte infiltration: Immerse the composite current collector in the electrolyte to ensure that it is completely infiltrated by the electrolyte. The electrolyte consists of a lithium salt and a solvent. The lithium salt is LiPF6 with a concentration of 1 mol / L. The solvent composition is a mixture of EC:DEC = 1:1, where 1:1 is the mass ratio of EC to DEC.
[0150] 2) Electrode and battery assembly: Metal electrodes are placed on both sides of the composite current collector, one electrode is a copper electrode and the other electrode is an aluminum electrode, and then the entire structure is sealed to form an electrochemical cell.
[0151] 3) Electrochemical impedance spectroscopy (EIS) measurement: Apply a small amplitude AC voltage in the frequency range of 0.01Hz to 100kHz to measure the impedance of the composite current collector. By analyzing the impedance spectrum, the resistance and capacitance characteristics of the composite current collector can be obtained, and then the ionic conductivity σ can be calculated. ion Specifically, the low-frequency line segment in the electrochemical impedance spectrum is extended to intersect with the X-axis, and the difference between the intersection point and the intersection point of the high-frequency line segment and the X-axis is obtained. Three times this value is the ionic impedance σ of the composite current collector. ion .
[0152] Electronic conductivity test:
[0153] The four-probe test method is used, and the specific steps are as follows:
[0154] The needles of the four probes are arranged in a straight line at equal distances, and are respectively recorded as probes 1, 2, 3, and 4. The radius of curvature of the probe tips is 25 μm, and the probe spacing is fixed at 1 mm. A pressure of 150 g is applied between the probes and the first conductive layer of the composite current collector, and the voltage V and current value I are obtained by the voltmeter and ammeter to calculate the electronic conductivity σ of the composite current collector. e =1 / ((π / ln2)×(V / I)), π is the ratio of a circle to a circle.
[0155] Example 1-1
[0156] <Preparation of negative electrode sheet>
[0157] Preparation of substrate: Polymer polyvinylidene fluoride-hexafluoroethylene, inorganic solid electrolyte Li7La3Zr2O 12Mix with solvent DMF and disperse evenly to obtain a mixed solution with a solid content of 40wt%. Apply the mixed solution on a polyethylene terephthalate substrate, dry at 80°C and a vacuum degree of 0.02Mpa, and then peel off the base film to obtain a composite solid electrolyte membrane, i.e., a substrate. The thickness of the substrate is L2 = 8μm, and the porosity is T 22 =40%, size is 47mm×44mm.
[0158] Preparation of composite current collector A: Cu is disposed on one surface of the substrate by magnetron sputtering to obtain composite current collector A. The Cu metal layer is used as the first conductive layer, and the thickness of the first conductive layer is L 11 =1μm, porosity T 11 =30%; the porosity of the composite current collector A is T3 =37% and the thickness is L3 =9 μm.
[0159] The negative electrode active material artificial graphite, conductive agent, and binder are mixed in a mass ratio of 95:3:2, and deionized water is added as a solvent to prepare a slurry with a solid content of 45wt%, and the negative electrode slurry is obtained after being stirred evenly by a vacuum mixer. Among them, the binder is a mixture of styrene-butadiene rubber and carboxymethyl cellulose in a mass ratio of 1:1.
[0160] The negative electrode slurry was evenly coated on the surface of the first conductive layer of the composite current collector A prepared above, dried at 120° C., and cold pressed to obtain a negative electrode sheet. The thickness of the negative electrode material layer was 80 μm.
[0161] <Preparation of positive electrode sheet>
[0162] Preparation of substrate: The same as the preparation of substrate in <Preparation of negative electrode sheet>.
[0163] Preparation of composite current collector B: Al is disposed on one surface of the substrate by magnetron sputtering to obtain composite current collector B. The Al metal layer is used as the second conductive layer, and the thickness of the second conductive layer is L 12 =1.2μm, porosity T 12 =30%; the porosity T3 of the composite current collector B is 36%, and the thickness L3 is 9.2 μm.
[0164] The positive electrode active material LiCoO2, the conductive agent conductive carbon black, and the binder polyvinylidene fluoride are mixed in a mass ratio of 94.8:2.8:2.4, and N-methylpyrrolidone (NMP) is added as a solvent to prepare a slurry with a solid content of 75wt%. After vacuum stirring, the positive electrode slurry is obtained.
[0165] The positive electrode slurry was evenly coated on the surface of the second conductive layer of the composite current collector B prepared above, dried at 120° C., and cold pressed to obtain a positive electrode sheet. The thickness of the positive electrode material layer was 100 μm.
[0166] <Preparation of Electrolyte>
[0167] In an environment with a water content of less than 10ppm, ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), propyl propionate (PP), and vinylene carbonate (VC) are mixed in a mass ratio of 20:30:20:28:2 to obtain an organic solvent, and then electrolyte salt LiPF6 is added to the organic solvent and mixed evenly to obtain an electrolyte solution. The mass percentage of the electrolyte salt in the electrolyte salt is 1 mol / L.
[0168] <Diaphragm>
[0169] A porous polyethylene film with a thickness of 7 μm (provided by Celgard Company) was used as a separator.
[0170] <Preparation of lithium-ion batteries>
[0171] The composite pole piece, separator and composite pole piece prepared above are stacked in order and wound to obtain an electrode assembly. The electrode assembly is placed in an aluminum-plastic film packaging bag, and the water is removed at 80°C, and the prepared electrolyte is injected. After vacuum packaging, standing, forming, degassing, trimming and other processes, a lithium-ion battery is obtained. Among them, the upper limit voltage of the formation is 4.15V, the formation temperature is 70°C, and the formation standing time is 2h.
[0172] Example 2 to Example 27
[0173] Except for adjusting the relevant preparation parameters according to Table 1 and Table 2, the rest is the same as Example 1.
[0174] Embodiment 28
[0175] Except for preparing the composite current collector according to the following steps, the rest is the same as Example 1:
[0176] The preparation of the substrate is the same as in Example 1.
[0177] Mix carbon nanotubes and adhesive styrene butadiene rubber in a mass ratio of 6:4, add deionized water to prepare a slurry with a solid content of 15%, and stir evenly to obtain a first conductive layer slurry. Mix carbon nanotubes and adhesive styrene butadiene rubber in a mass ratio of 1:1, add deionized water to prepare a slurry with a solid content of 15%, and stir evenly to obtain a second conductive layer slurry. Coat the first conductive layer slurry on one surface of the porous electrolyte membrane by gravure coating, dry, and obtain a composite current collector A. Coat the second conductive layer slurry on one surface of the porous electrolyte membrane by gravure coating, dry, and obtain a composite current collector B. The first conductive layer and the second conductive layer are conductive carbon layers, and the thickness of the first conductive layer is L 11 =0.6μm, porosity T 11 =30%, the thickness of the second conductive layer L 12 =0.7μm, porosity T 12 =30%.
[0178] Embodiment 29
[0179] The same as Example 28 except that the mass ratio of carbon nanotubes to adhesive in the first conductive layer slurry is 75:25 and the mass ratio of carbon nanotubes to adhesive in the second conductive layer slurry is 62.5:37.5.
[0180] Embodiment 30
[0181] The same as Example 28 except that the mass ratio of carbon nanotubes to adhesive in the first conductive layer slurry is 95:5 and the mass ratio of carbon nanotubes to adhesive in the second conductive layer slurry is 79:21.
[0182] Embodiment 31
[0183] The preparation of the positive electrode slurry, the negative electrode slurry, the electrolyte and the separator is the same as in Example 1, and the rest is prepared according to the following steps:
[0184] <Preparation of Composite Current Collector>
[0185] Preparation of substrate: In addition to the polymer polyvinylidene fluoride-hexafluoroethylene and the inorganic solid electrolyte Li7La3Zr2O 12 Except that the mass percentage of is shown in Table 1, the remaining preparation steps are the same as those in Example 1.
[0186] Al and Cu are respectively disposed on the two surfaces of the substrate by magnetron sputtering to obtain a composite current collector. The Cu metal layer is used as the first conductive layer, and the thickness of the first conductive layer is L 11 =1μm, porosity T 11 =30%; the Al metal layer is used as the second conductive layer, and the thickness of the second conductive layer is L 12 =1.2μm, porosity T 12=30%; the porosity of the composite current collector is T3 =34%, and the thickness is L3 =10.2 μm.
[0187] <Preparation of composite pole piece>
[0188] The negative electrode slurry is evenly coated on the surface of the first conductive layer of the composite current collector prepared above, and dried at 120°C to obtain a composite current collector coated with a negative electrode material layer; the positive electrode slurry is evenly coated on the surface of the second conductive layer of the composite current collector prepared above, dried at 120°C, and cold pressed to obtain a composite electrode sheet. The thickness of the positive electrode material layer is 100 μm, and the thickness of the negative electrode material layer is 80 μm.
[0189] <Preparation of lithium-ion batteries>
[0190] The composite electrode sheet, diaphragm and composite electrode sheet prepared above are stacked in order to obtain an electrode assembly. The electrode assembly is placed in an aluminum-plastic film packaging bag, and the water is removed at 80°C, and the prepared electrolyte is injected. After vacuum packaging, standing, forming, degassing, trimming and other processes, a lithium-ion battery is obtained. Among them, the upper limit voltage of the formation is 4.15V, the formation temperature is 70°C, and the formation standing time is 2h.
[0191] Embodiment 32
[0192] <Preparation of negative electrode sheet> The preparation of positive electrode slurry, electrolyte and separator is the same as in Example 1, and the rest is prepared according to the following steps:
[0193] <Preparation of positive electrode sheet>
[0194] A 12 μm thick aluminum foil was used as the positive electrode current collector, and the positive electrode slurry was evenly coated on one surface of the positive electrode current collector and dried at 120°C; the above steps were repeated on the other surface of the aluminum foil, and then cold pressed to obtain a positive electrode sheet. The thickness of the single-layer positive electrode material layer was 100 μm.
[0195] <Preparation of lithium-ion batteries>
[0196] The positive electrode sheet, separator and negative electrode sheet prepared above are stacked in order to obtain an electrode assembly, wherein a separator is provided between the positive electrode sheet and the negative electrode sheet. The electrode assembly is placed in an aluminum-plastic film packaging bag, and the water is removed at 80°C, and the prepared electrolyte is injected, and a lithium-ion battery is obtained through vacuum packaging, standing, formation, degassing, trimming and other processes. Among them, the formation upper limit voltage is 4.15V, the formation temperature is 70°C, and the formation standing time is 2h.
[0197] Comparative Example 1
[0198] Except for preparing the negative electrode sheet according to the following steps, the rest is the same as Example 32:
[0199] <Preparation of negative electrode sheet>
[0200] The preparation of the negative electrode slurry is the same as that in Example 1.
[0201] A copper foil with a thickness of 8 μm was used as the negative electrode current collector, and the negative electrode slurry was evenly coated on one surface of the negative electrode current collector and dried at 120°C; the above steps were repeated on the other surface of the aluminum foil, and then cold pressed to obtain a negative electrode sheet. The thickness of a single negative electrode material layer was 80 μm.
[0202] The preparation parameters and performance tests of various embodiments and comparative examples are shown in Tables 1 and 2.
[0203]
[0204]
[0205]
[0206]
[0207] Referring to Table 1 and Table 2, it can be seen from Examples 1 to 32 and Comparative Example 1 that the lithium ion batteries in the examples all include a composite current collector, which has high ionic conductivity and electronic conductivity, indicating good ionic conductivity and electrical conductivity; the lithium ion battery in the comparative example does not include a composite current collector, wherein the negative electrode current collector has no ionic conductivity and only electrical conductivity. In the lithium ion battery in the example, the minimum value of I1 / I2 in the negative electrode material layer is the same as the value of I1 / I2 at Z=0.5L±0.1L, that is, the state of charge is lowest in the middle region of the negative electrode material layer, while the minimum value of I1 / I2 in the comparative example is different from the value of I1 / I2 at Z=0.5L±0.1L; and the difference X between the maximum and minimum values of I1 / I2 in the negative electrode material layer of the example is also significantly smaller than that of the comparative example, indicating that the overall non-uniformity of the state of charge of the negative electrode material layer in the example is improved. At the same time, the discharge capacity retention rate of the lithium ion battery in the embodiment at 3C and 5C is also higher than that of the comparative example, indicating that the rate performance of the lithium ion battery in the embodiment is improved compared with that of the comparative example.
[0208] Specifically, Figure 4 and Figure 5As shown, for the negative electrode material layer of Example 1, the minimum value of I1 / I2 is located in the middle area of the negative electrode material layer, and the values of I1 / I2 are larger on both sides along the thickness direction of the negative electrode material layer; for the negative electrode material layer of Comparative Example 1, the minimum value of I1 / I2 is located on the side of the negative electrode material layer close to the negative electrode current collector, and the maximum value of I1 / I2 is located on the side of the negative electrode material layer far from the negative electrode current collector, which indicates that the overall charge state non-uniformity of the negative electrode material layer in Example 1 is improved compared with that in Comparative Example 1.
[0209] The type of substrate in the composite current collector usually affects the ion conductivity of the composite current collector, and thus affects the rate performance of the lithium-ion battery. Referring to Table 1, it can be seen from Examples 1 to 17 that when the type of substrate is within the scope of the present application, the composite current collector obtained has a higher ionic conductivity and electronic conductivity, the minimum value of I1 / I2 in the negative electrode material layer is the same as the value of I1 / I2 at Z=0.5L±0.1L, and the difference X is small. At the same time, the discharge capacity retention rate of the lithium-ion battery at 3C and 5C is also high, indicating that the overall charge state uniformity of the negative electrode material layer is good, and the lithium-ion battery has good rate performance.
[0210] The thickness and porosity of the substrate will affect the thickness and porosity of the composite current collector, which will usually affect the ion conductivity of the composite current collector, and thus affect the rate performance of the lithium-ion battery. Referring to Table 1, it can be seen from Example 1, Example 7 to Example 8, and Example 17 to Example 21 that when the thickness and porosity of the substrate are within the scope of the present application, the thickness and porosity of the obtained composite current collector are also within the scope of the present application, and it has high ionic conductivity and electronic conductivity, and the minimum value of I1 / I2 in the negative electrode material layer is the same as the value of I1 / I2 at Z=0.5L±0.1L, and the difference X is small. At the same time, the discharge capacity retention rate of the lithium-ion battery at 3C and 5C is also high, indicating that the overall charge state uniformity of the negative electrode material layer is good, and the lithium-ion battery has good rate performance.
[0211] The thickness and porosity of the conductive layer will affect the thickness and porosity of the composite current collector, and the thickness and porosity of the composite current collector will usually affect the ion conductivity and electrical conductivity of the composite current collector, and thus affect the rate performance of the lithium ion battery. Referring to Table 2, it can be seen from Example 1, Example 17 to Example 20, and Example 22 to Example 23 that when the thickness and porosity of the conductive layer are within the scope of the present application, the thickness and porosity of the obtained composite current collector are also within the scope of the present application, and it has high ionic conductivity and electronic conductivity, and the minimum value of I1 / I2 in the negative electrode material layer is the same as the value of I1 / I2 at Z=0.5L±0.1L, and the difference X is small. At the same time, the discharge capacity retention rate of the lithium ion battery at 3C and 5C is also high, indicating that the overall charge state uniformity of the negative electrode material layer is good, and the lithium ion battery has good rate performance.
[0212] The type of conductive layer usually affects the ion conductivity and electrical conductivity of the composite current collector, and thus affects the rate performance of the lithium-ion battery. Referring to Table 2, it can be seen from Examples 1, 28 to 30 that when the type of the conductive layer is within the scope of the present application, the composite current collector obtained has a higher ionic conductivity and electronic conductivity, the minimum value of I1 / I2 in the negative electrode material layer is the same as the value of I1 / I2 at Z=0.5L±0.1L, and the difference X is small. At the same time, the discharge capacity retention rate of the lithium-ion battery at 3C and 5C is also high, indicating that the overall charge state uniformity of the negative electrode material layer is good, and the lithium-ion battery has good rate performance.
[0213] The thickness of the negative electrode material layer usually affects the rate performance of the lithium-ion battery. Referring to Table 2, it can be seen from Examples 1, 24 to 27 that when the thickness of the negative electrode material layer is within the range of the present application, the E g / A 1g The minimum value is the same as the value of I1 / I2 at Z=0.5L±0.1L, and the difference X is small. At the same time, the discharge capacity retention rate of the lithium-ion battery at 3C and 5C is also high, indicating that the overall charge state uniformity of the negative electrode material layer is good, and the lithium-ion battery has good rate performance.
[0214] It can be seen from Example 1, Example 31 and Example 32 that when the composite current collector is used for the positive electrode sheet, the negative electrode sheet and the composite electrode sheet, the obtained lithium-ion batteries have good rate performance.
[0215] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.
[0216] The terms "one of", "one of", "a kind of" or other similar terms connected to the elements refer to any one of the listed elements. For example, "one of A or B" means only A or only B; as another example, "one of A, B, and C" means only A, only B, or only C. The terms "at least one of", "at least one of", "at least one of" or other similar terms connected to the elements refer to any combination of the listed elements. For example, "at least one of A or B" means only A, only B, A and B. As another example, "at least one of A, B, or C" means only A, only B, only C, only A and B, only A and C, only B and C, A, B, and C.
[0217] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. An electrochemical device, comprising a pole piece, the pole piece comprising a composite current collector and a negative electrode material layer located on the surface of the composite current collector, the XRD spectrum of the negative electrode material layer having a characteristic peak intensity of I1 at 23.5° to 24.5° and a characteristic peak intensity of I2 at 24.5° to 25.5°; The thickness of the negative electrode material layer is L μm, and along the thickness direction of the negative electrode material layer, the distance from any point in the negative electrode material layer to the negative electrode current collector is Z μm, and at Z=0.5L±0.1L, I1 / I2 reaches a minimum value; The ionic conductivity σ of the composite current collector ion For 10 -4 S / cm≤σ ion ≤10 -1 S / cm.
2. The electrochemical device according to claim 1, wherein: At Z=0.5L±0.1L, 10≤I1 / I2≤30.
3. The electrochemical device according to claim 1, wherein When the charging rate is 5C, along the thickness direction of the negative electrode material layer, the difference between the maximum value and the minimum value of I1 / I2 in the negative electrode material layer is less than or equal to 30.
4. The electrochemical device according to claim 1, wherein The thickness of the negative electrode material layer is 30 μm to 180 μm.
5. The electrochemical device according to claim 1, wherein The thickness of the negative electrode material layer is 40 μm to 120 μm.
6. The electrochemical device according to claim 1, wherein The negative electrode material layer includes a negative electrode active material, and the negative electrode active material includes at least one of graphite, a graphite silicon-carbon composite material, a graphite hard carbon composite material, or a graphite soft carbon composite material.
7. The electrochemical device according to claim 1, wherein: The composite current collector comprises a substrate and a conductive layer located on the surface of the substrate, the substrate comprises any one of a porous polymer membrane, a polymer solid electrolyte membrane or a composite solid electrolyte membrane, and the conductive layer is selected from a metal layer or a conductive carbon layer.
8. The electrochemical device according to claim 7, wherein: The porous polymer membrane includes a high molecular polymer; The polymer solid electrolyte membrane comprises a lithium salt and the high molecular polymer; The composite solid electrolyte membrane includes an inorganic solid electrolyte and the high molecular polymer.
9. The electrochemical device according to claim 8, wherein: The high molecular polymer includes at least one of polypropylene, polyethylene terephthalate, polystyrene, polyethylene, poly(p-phenylene terephthalamide), polyethylene oxide, poly(methyl methacrylate), polyacrylonitrile, polyvinylidene fluoride or polyvinylidene fluoride-hexafluoroethylene; The lithium salt includes at least one of LiPF6, LiN(CF3SO2)2, LiN(FSO2)2, LiCF3SO3 or LiClO4; The inorganic solid electrolyte includes at least one of a sulfide solid electrolyte or an oxide solid electrolyte; The sulfide solid electrolyte includes (100-x1)Li2S-x1P2S5, Li 4-x2 Ge 1-x2 P x2 S4、LiPSCl 0.8 、LiPSCl 1.3 、LiPSCl 1.5 or LiPSCl 1.6 At least one of; wherein, 1≤x1≤99, 0.01≤x2≤0.99; The oxide solid electrolyte includes Li 1+x3 M x Ti 2-x3 (PO4)3、Li 1.5 Z 0.5 Ge 1.5 (PO4)3、Li 7- 3x4 Ga x4 La3Zr2O 12 、Li7La3Zr2O 12 , Li 6.55 Ga 0.15 La3Zr2O 12 or Li 0.34 La 0.51 TiO 2.94 At least one of; wherein, M includes at least one of Al, Cr, Ga, Fe, Sc, In, Lu, Y or La, 0≤x3≤0.5, and Z includes at least one of Al, Cr, Ga, Fe, Sc, In, 0.1≤x4≤0.
4.
10. The electrochemical device according to any one of claims 7 to 9, wherein: The material of the metal layer includes any one of copper, nickel or silver.
11. The electrochemical device according to any one of claims 7 to 9, wherein: The conductive carbon layer includes conductive carbon and a binder, wherein the conductive carbon includes at least one of conductive carbon black, carbon nanotubes or conductive graphite, and the binder includes at least one of polyvinylidene fluoride, styrene-butadiene rubber or acrylate; The mass percentage of the conductive carbon in the conductive carbon layer is W1%, 50≤W1≤95.
12. The electrochemical device according to any one of claims 7 to 9, wherein: The thickness L1 of the conductive layer is 0.1 μm to 5 μm.
13. The electrochemical device according to any one of claims 7 to 9, wherein: The composite current collector satisfies at least one of the following characteristics: (a) the porosity T1 of the conductive layer is 10% to 75%; (b) the thickness L3 of the composite current collector is 2.5 μm to 20 μm, and the thickness L2 of the substrate is 2 μm to 10 μm; (c) the porosity T3 of the composite current collector is 5% to 80%; (d) The porosity T of the porous polymer membrane 21 20% to 90%; (e) The porosity T of the polymer solid electrolyte membrane or the composite solid electrolyte membrane 22 0% to 60%; (f) The electronic conductivity of the composite current collector is σ e , 10 -8 S / m≤σ e ≤10 8 S / m.
14. The electrochemical device according to any one of claims 7 to 9, wherein: The composite current collector meets at least one of the following characteristics: (a) the thickness L3 of the composite current collector is 4 μm to 16 μm; (b) The electronic conductivity of the composite current collector is σ e , 10 -3 S / m≤σ e ≤10 7 S / m.
15. The electrochemical device according to any one of claims 1 to 9, which satisfies one of the following characteristics: (a) the electrode sheet is a negative electrode sheet, the negative electrode material layer is located on one surface of the composite current collector, the electrochemical device further comprises a positive electrode sheet, the positive electrode sheet comprises a positive current collector and positive electrode material layers located on both surfaces of the positive current collector; a separator is included between the negative electrode material layer and the positive electrode material layer, the positive current collector is selected from metal foil, the material of the metal foil is selected from aluminum, nickel, copper or silver; (b) the electrode sheet is a negative electrode sheet, the negative electrode material layer is located on one surface of the composite current collector, the electrochemical device further comprises a positive electrode sheet, the positive electrode sheet comprises the composite current collector and the positive electrode material layer located on one surface of the composite current collector, the positive electrode material layer is adjacent to a surface of the negative electrode sheet away from the negative electrode material layer, and the negative electrode material layer is adjacent to a surface of the positive electrode sheet away from the positive electrode material layer; (c) The electrode sheet is a composite electrode sheet, and the composite electrode sheet further includes a negative electrode material layer. The positive electrode material layer is located on one surface of the composite current collector, and the negative electrode material layer is located on the other surface of the composite current collector.
16. An electronic device comprising the electrochemical device according to any one of claims 1 to 15.